EVALUATION OF FLOOD MANAGEMENT POLICIES IN EAST BARITO REGENCY CENTRAL KALIMANTAN - Agus Sukamat; Reno Affrian (PT. Antis International Publisher, 2026)
Objective: This research aims to evaluate the flood management policy in East Barito Regency by assessing the alignment between policy objectives, on-the-ground implementation, and the results achieved. Method: The research uses a descriptive qualitative approach with data collection methods including in-depth interviews, observation, and document study. Data analysis was conducted using a policy evaluation framework that included aspects of effectiveness, efficiency, adequacy, equity, responsiveness, and timeliness. Results: Flooding is one of the hydrometeorological disasters that repeatedly occurs in East Barito Regency, Central Kalimantan, and causes significant social, economic, and environmental impacts. Local governments have implemented various flood management policies thru structural and non-structural programs, but the effectiveness of these policies is still debated. The research results indicate that flood management policies have been implemented according to the regulatory framework, but they are not yet optimal in sustainably reducing flood risks and impacts. The main obstacles include limited cross-sectoral coordination, the dominance of structural approaches, weak spatial planning control, and minimal community participation. Novelty: This research recommends strengthening flood management policies based on disaster risk reduction and multi-stakeholder collaboration.